Development of creative potential of primary school children in the system of advanced education for sustainable development (Actual Problems of Psychology in Educational Institutions, 2018)
The article presents an analysis of the problem of thedevelopment of creative thinking of younger schoolchildren in the context ofeducation reform. Іt is noted that optimal conditions for the development ofcreative thinking of schoolchildren are provided by the education model forsustainable development. The author proves the importance of the formation ofa productive educational space for the development of the creative potential ofschoolchildren. Based on the analysis of theoretical positions, the features of thedevelopment of creative thinking of younger schoolchildren are analyzed. Theconclusion is made about the need for targeted support of this process in thecontext of sustainable development education.